"I just feel so guilty": The role of introjected regulation in linking appearance goals for exercise with women's body image. (March 2017) - Hurst, Megan; Dittmar, Helga; Banerjee, Robin; Bond, Rod
Highlights: We investigate the link between women's appearance goals for exercise and body image. The paper employs correlational and experimental methods to explore this link. Guilt-related exercise motivation mediated the appearance goals and body image link. Women primed with exercise-related guilt experienced greater post-test body anxiety. Abstract: Appearance goals for exercise are consistently associated with negative body image, but research has yet to consider the processes that link these two variables. Self-determination theory offers one such process: introjected (guilt-based) regulation of exercise behavior. Study 1 investigated these relationships within a cross-sectional sample of female UK students ( n = 215, 17–30 years). Appearance goals were indirectly, negatively associated with body image due to links with introjected regulation. Study 2 experimentally tested this pathway, manipulating guilt relating to exercise and appearance goals independently and assessing post-test guilt and body anxiety ( n = 165, 18–27 years). The guilt manipulation significantly increased post-test feelings of guilt, and these increases were associated with increased post-test body anxiety, but only for participants in the guilt condition. The implications of these findings for self-determination theory and the importance of guilt for the body image literature are discussed.